PERANCANGAN MEDIA PEMBELAJARAN TUTORIAL AUTO CAD 2D MENGGAMBAR TAMPAK DAN POTONGAN BANGUNAN - ADI KURNIAWAN, INSAN (Pendidikan Teknik Bangunan, 2013)
The purpose of this study is : Designing 2D AutoCAD tutorial learning media, particularly on the subject of drawing look and pieces of the building know the outcome of the process of making to AutoCAD tutorial video and produce learning media devices are valid and deserve to be used as a learning media AutoCAD. The research methodusedin this researchwas Research & Development (R&D) method. The research wasconductedon the di SMK N 5 Surakarta. Design done by taking a path that includes the development of assessment procedures subjects AutoCAD, user assessment of media types, the assessment of media makers, and create a storyboard. The circuit design includes the collection of products made with the object of media support, the design of video learning, revision, validation, revision, testing, and evaluation. Success criteria of this research refers to the successful development and validation testing of products. The successful achievement of the design of products obtained from the use of media that includes: (1) the suitability aspects of substance experts, media specialists and experts intruksional learning. (2) The test is limited. (3) field test. The results showed that the AutoCAD 2D tutorial learning media drawing looks and pieces of the building proved to be fit for use as a AutoCAD media learning and can help students in understanding the material well. This is evident from the results of the test expert, limited testing and field testing. For media expert scoring (89,56%), a substance gives a score (90%), instructional specialists provide a score (90%), while the limited test data obtained by interviewing a few samples of students and one teacher stated greatly helped. Field test data obtained by questionnaires 31 respondents and interview some of the sample of students who declare helped as much as 85% and declared not helped as much as 15%. It means learning video is acceptable as a medium of teaching in subjects AutoCAD drawing particularly on the subject of looks and pieces on the building. Conclusion this study shows learning media products such as video tutorial learning model can help the delivery of content on the subjects AutoCAD particular on the subject of looks and pieces on the building. This learning video is an efficient, effective and precise media, so that the development model of learning video can be recommended as one of the new innovations in the learning media subjects AutoCAD particular on the subject of looks and pieces on the building. Keywords: design of learning videos, AutoCAD, drawing looks and pieces